Design and dynamic analysis of a 4-story multifamily building without basement in the Province of Chanchamayo - Rupay Vargas , Marcos Josue (2024)
In the present investigation, the design of a 4-story building without a basement located in the Province of Chanchamayo of Peru was carried out, intended for a multi-family home made up of structural elements such as columns, beams, and plates, which each one was designed and modeled under the Peruvian Load Regulations E. 020, Earthquake-resistant Design E. 030, Reinforced Concrete E. 060, Masonry E. 070 and General Design Conditions A. 010. The use of these Standards is established in the National Building Regulations that allowed compliance with the objective of designing and carrying out the Dynamic Analysis of the Building under the Earthquake methodology, which is based on the Load factor and resistance design method. Modeling was carried out with the help of ETABS software to obtain results necessary for the design and analysis of the structure. Finally, it was obtained that the building will use the structural system for structural walls, which has a basic reduction coefficient equal to 6 and it is concluded that the methodology used allows guaranteeing the safety, functionality and quality service of a building.